Regulatory Analysis of Electronic Wallet - Intan Rachmadhani; Muhammad Insa Ansari; Teuku Saiful (International Journal of Law and Society, 2026)
The advancement of financial technology has resulted in the creation of electronic wallets that serve not only as payment instruments but also as platforms for electronic transactions and digital loan services. This situation engenders a conflict between the implementation and the prevailing regulation, specifically Bank Indonesia Regulation Number 18/40/PBI/2016 regarding Payment Transaction Processing, which raises concerns about legal certainty and user protection, particularly in relation to the delineation of supervisory authority between Bank Indonesia and the Financial Services Authority. This research aims to elucidate the regulation of electronic wallets in terms of legal clarity, legal protection, and oversight by the Financial Services Authority and Bank Indonesia concerning the adoption of electronic wallets. This study employs a normative legal methodology. Data is derived from secondary sources, encompassing primary, secondary, and tertiary legal literature. This study employs both a legislative and a conceptual methodology. The research findings suggest that the regulation of electronic wallets, as per Bank Indonesia Regulation, has not entirely met user requirements. Bank Indonesia Regulation Number 18/40/PBI/2016, on the Implementation of Payment Transaction Processing, does not explicitly address legal certainty and legal protection for users who deposit funds or utilise digital loan services on electronic wallets. This situation establishes a disparity between regulatory implementation and governing rules, which may result in insufficient oversight of electronic wallet operations and a discord of authority between Bank Indonesia and the Financial Services Authority regarding the supervision of financial transactions in Indonesia.